Perancangan Sistem Informasi Pariwisata Berbasis Web untuk Meningkatkan Minat Wisatawan: Studi Kasus: CV. Kibito Amona Nabire - Yulianus Pekei; Usman Arfan (Jurnal Teknologi dan Informatika, 2024)
Effective tourism information management is very important in supporting the promotion of tourist destinations and improving tourist experiences. This article discusses the development of a web-based Tourism Information System using the Agile method. This system is designed to provide comprehensive and real-time information about tourist destinations, including descriptions of places, facilities, event schedules, as well as reviews and ratings from visitors. The Agile method was chosen because of its flexibility which allows system development to be carried out iteratively and incrementally, involving user feedback at each stage of the development cycle. The development process starts from planning, followed by iteration which includes design, development, testing, and review. The conclusion of this research is that the application of the Agile method in developing a web-based Tourism Information System can increase development efficiency and system quality.